INSTITUTIONS, AND FIRMS' PERFORMANCES IN TRANSITION COUNTRIES: THE CASE OF THE SELECTED CESEE COUNTRIES (The South East European Journal of Economics and Business, 2018)
Institutional reforms in the countries of Central Eastern and South Eastern Europe (CESEE) brought about a redefinition of the role of the state, the market and the business sector. We assess the effects of various dimensions of the institutional environment on the labour productivity of manufacturing firms in selected CESEE countries by employing a multilevel model. Our findings reveal that the curbing of corruption and the provision of inter-industrial externalities through the development of a commercial and professional infrastructure have beneficial effects on firm productivity. At the same time, a stricter political and legal framework and the provision of R&D infrastructure have an adverse effect. Such a finding is typical for producers of standardised products in countries with low levels of legal framework development for which R&D and legal adjustments incur cost disadvantages. The implication is that institutional development should be accompanied by a strengthening of firms’ absorptive capacity in order for businesses to benefit from such changes.